Bilateral Genu Valgum in an Adolescent with Primary Hyperparathyroidism: A Case Report and Review of Literature - Lee, Siow Ping; Chai, Shu Teng; Loh, Leh Teng; Mohd Ali , Norhaliza (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Primary hyperparathyroidism in children and adolescents is rare and often symptomatic at presentation. A 15-year-old boy presented with bilateral genu valgum for two years. Biochemical results were consistent with primary hyperparathyroidism. Calcium levels normalized two months after removal of a left inferior parathyroid adenoma.